An industrial quality control study on Almazora Motors Corporation - Alsua, Agnes Eliza (College of Engineering, 2000)
Almazora Motors Corporation is a manufacturing company that specializes in the mass production of Asian Utility Vehicles (AUVs) or the L300 FB Body. The production of these L300 bodies includes several processes : stamping, sub and main assembly, pre-metal treatment, painting, de-waxing, and undercoats, trimming and decking. Several measures are undertaken to ensure the proper quality of the product. Some of these would be full and sampling inspections for raw materials, work-in-process and pre-delivery. The company holds product and quality specifications to guide and restrict variability within the units. With the use of statistical concepts and tools, Almazora's processes were analyzed and scrutinized for possible problems. Through the Failure Mode Effect and Criticality Analysis (FMECA), several areas for improvement have been found. It was determined that in the stamping process : 1) wave formations, 2) grinding marks and 3) dents were the most occuring and most serious. Ishikawa diagrams were administered in helping determine factors which may have caused the said problems. It was also discovered, that 4) thin paint was a recurring problem that needed to be addressed. Further analysis of the problem required other tools such as the Ishikawa and Streamline analysis diagrams. These four main problems have been analyzed and broken down for further study that would lead to conducting statistical quality control tools. Statistical process control was administered with the use of three attribute control charts (c-chat) for the stamping process problems-grinding, wave and dents-and two variable control charts (moving range) for the thin paint problem (after first primer application and after oven to dry-both under paint thickness category in the painting process.) It resulted with an out of control chart in the "after oven" process and was therefore recomputed with the necessary adjustments made.The process capability was studied using two methods. The first method involved the normal probability plots. For the "after oven paint thicnkess", subcontractors, denoted as RT and LC, both resulted into a normally distributed plot. From the "first primer process" only supplier RT showed signs of normality. No inferences could be generated regarding the non-normal distribution of the LC thus other methods should be used. The second method in studying the process capability was the process capability ratio. For the painting process, all levels were low enough not to have reached the suggested ratio of at least 1.45 for one-sided specifications. It was discovered from the quality cost analysis that internal and external failure costs are not recorded by the company. Appraisal costs and prevention costs are not separated from other accounts to form a quality cost audit. The team therefore recommends that the company undertake a "methods engineering" study to improve on the present system in production for "efficiency and effectivity." Ergonomic considerations should also be noted since this contributes to the effectivity of the work force. Aside from that, it is also suggested that Almazora start with basic quality control tools such as histograms, pareto charts, Ishikawa and streamline and enforce them strictly so as to improve the quality system. They may use these tools where they find it appropriate since the company holds historical data that may give vital information on future improvements. From there, the company may move further into introducing the use of more advanced statistical quality control techniques by administering control charts that would fit for every process involved. Almazora should also consider to regularly monitor their process capability to see whether the company is headed into a more improved state. The inspections being conducted do not suffice if the data gathered are not put into proper use for analysis. Since the company involves itself with sampling, quality control inspectors may want to study topics and concepts regarding acceptance sampling to determine whether inspection methods are at its optimal level.